Cardiovascular Events and Related Factors in Routine Hemodialysis Patients with Chronic Kidney Disease (CKD) at a Tertiary Care Hospital in Pakistan: Cardiovascular Events in Hemodialysis Patients - Kumar Karmani, Jais; Ali, Mohammad (Pakistan Journal of Health Sciences, 2024)
Cardiovascular-related events were a significant problem in patients receiving dialysis. These patients were at a higher risk due to the complex interplay of factors such as hypertension, anemia, and other comorbid conditions. Objective: To find the cardiovascular events and related factors in routine hemodialysis patients with Chronic Kidney Disease (CKD) at a tertiary care hospital in Pakistan. Methods: This Cross-sectional retrospective study conducted in routine dialysis patients in a tertiary care hospital, from October 2022 to December 2023. Patients that experienced cardiovascular events were included in the study, with those not experiencing any cardiovascular event were excluded from the research. Informed consent was taken from patients to collect the data. Results: The study included 255 dialysis patients (mean age 60.5 years ±10.2), with 128 males (50.1%) and 127 females (49.8%). Heart failure was the most common cardiovascular event, followed by pleural effusion, while sudden cardiac death was one of the least frequent but significant. Hypertension and anemia were the major risk factors for cardiovascular events in end-stage renal disease, with thyroid function issues being the least associated. Conclusions: Managing CKD and cardiovascular risks in Peritoneal Dialysis (PD) and Hemodialysis (HD) patients requires strict control of blood pressure, lipids, and glucose, and careful monitoring of volume status. Lifestyle changes and advancements in dialysis equipment show promise, but more research is needed to optimize treatment and improve outcomes. Clinicians can reduce cardiovascular risk and enhance life expectancy and quality of life by addressing these factors.